2014
DOI: 10.1111/1471-0307.12164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fat replacers on the chemical, textural and sensory properties of low‐fat Beyaz pickled cheese produced from ewe's milk

Abstract: In this study, low-fat Beyaz pickled cheeses were produced from ewe's milk using a protein-based fat replacer (1.0% w/w Simplesse â ), a carbohydrate-based fat replacer (0.5% w/w Maltrin â ) and a blend of both (0.5% w/w Simplesse â + 0.25% w/w Maltrin â ). The chemical, textural and sensory properties of cheeses were examined during storage for 60 days. The use of fat replacers affected chemical (except pH and acidity), textural and sensory properties of the cheeses. The cheeses produced with Simplesse â (Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…In PPC5 and PPC6 it was further hydrolyzed as indicated by the band below the αs1-I-CN. This behavior can be explained taking into account that αS1-I-casein is the fragment (f24-199) of αs1-casein formed by initial cleavage and is susceptible to further proteolytic attack by different proteinases and peptidases resulting in smaller fragments which disappear virtually in the later Pizza cheese blends (Akin and Kirmaci, 2015). The degradation is more noticeable in the PCB with four months ripened Cheddar cheese as compared to two months ripened Cheddar cheese.…”
Section: Urea Polyacrylamide Gel Electrophoresis (Urea-page)mentioning
confidence: 99%
“…In PPC5 and PPC6 it was further hydrolyzed as indicated by the band below the αs1-I-CN. This behavior can be explained taking into account that αS1-I-casein is the fragment (f24-199) of αs1-casein formed by initial cleavage and is susceptible to further proteolytic attack by different proteinases and peptidases resulting in smaller fragments which disappear virtually in the later Pizza cheese blends (Akin and Kirmaci, 2015). The degradation is more noticeable in the PCB with four months ripened Cheddar cheese as compared to two months ripened Cheddar cheese.…”
Section: Urea Polyacrylamide Gel Electrophoresis (Urea-page)mentioning
confidence: 99%
“…Additionally, the relationship observed between fat content and texture during the season was in accordance with the results obtained in previous studies. As fat content increases, cheeses show lower values for hardness and springiness [47,48].…”
Section: Cheesementioning
confidence: 99%
“…Low-fat Beyaz cheeses were manufactured using as raw materials: ewe's milk, Simplesse ® (protein-based replacer), Maltrin ® (carbohydrate-based fat replacer) and a blend of both. The cheeses produced with Simplesse ® were similar to cheese without replacers and obtained the highest sensory acceptance (Akin, 2015) A non-fat goats' milk yogurt was obtained by adding heat-treated whey protein concentrate (HWPC) as a fat mimetic and pectin as a thickening substance. The results showed that the non-fat goats' milk yogurt made with 1.2% HWPC and 0.35% pectin presented higher viscosity compared to the other yogurts.…”
Section: Ways To Reduce Fat Content In Dairy Productsmentioning
confidence: 99%
“…Nowadays people are interested in foods with bioactive components which provide health benefits (Cofrades et al, 2008). In foods, an essential component is fat with roles in development of flavour, texture, juiciness and appearance (Akin et al, 2015), (Choi et al, 2010). Lipids are also responsible in product processing for cooking yield and water holding capacity (Choi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%